Effects of cytokine hemadsorption as salvage therapy on common laboratory parameters in patients with life-threatening COVID-19 - Uysal, Serhat; Merter, Mustafa; Uysal, Ayse; Akbulut, Ayhan (Pergamon-Elsevier Science Ltd, 2023)
Background: The COVID-19 pandemic has led to emergency approval of treatment modalities unusual for viruses, such as therapeutic cytokine Hemadsorption(HA). This study aims to investigate the experience of salvage HA therapy and the effect of HA on routine laboratory tests.Methods: Life-threatening COVID-19 patients followed up between April 2020 and October 2022 who underwent HA salvage therapy were retrospectively enrolled. Data derived from the medical records were evaluated to meet the assumptions of statistical tests, and those that met the relevant statistical rules were selected for further analysis. Tests of Wilcoxon, Paired-T, and repeated measures-ANOVA were used to analyse the laboratory tests performed before and after HA among the surviving and nonsurviving patients. P < 0.05 was selected for the statistical significance of the alpha.Results: A total of 55 patients were enrolled in the study. Fibrinogen (p = 0.007), lactate dehydrogenase (LDH) (p = 0.021), C-reactive protein (CRP) (p < 0.0001), and platelet (PLT) (p = 0.046) levels showed a significant decrease with the HA effect. WBC (p = 0.209), lymphocyte (p = 0.135), procalcitonin (PCT) (p = 0.424), ferritin (p = 0.298), and D-dimer (p = 0.391) levels were not affected by HA. Ferritin level was significantly affected by survival status (p = 0.010). All patients tolerated HA well, and 16.4 % (n = 9) of the patients with life-threatening COVID-19 survived.Conclusion: HA is well tolerated even when used as a last option. However, HA may not affect WBC, lymphocyte, and D-dimer levels. In contrast, the effect of HA could limit the benefits of LDH, CRP, and fibrinogen in various clinical assessments. This study suggests that HA treatment could be beneficial even if selected as a salvage therapy
Keywords: Cytokine adsorption; COVID-19; Fibrinogen; Hemadsorption; Lactate dehydrogenase; Creactive protein; Platelet; Therapeutic adsorption